Prevalence of pelvic floor dysfunction in women attending obstetrics and gynaecology OPD at PES Institute of Medical Sciences asnd Research, Kuppam - Gaddam, Ramya; Gangadharan, Keshav; Shivaraju, Pradeep; Basappa, Pavan Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Millions of women are affected with pelvic floor dysfunction globally. But when the literature was reviewed, studies assessing the prevalence of PFD (pelvic floor dysfunction) and related factors were limited in India. Hence the present study was undertaken to assess the prevalence of PFD. Methods: 300 women aged 18-70years attending Obstetrics and Gynaecology OPD at Kuppam were interviewed and details like age, number of children, mode of delivery, BMI, education, occupation as primary outcome variables and type of pelvic floor dysfunction as explanatory variable were collected using a semi structured questionnaire. Frequency and proportions were calculated for quantitative variables and Chi-square test was used for comparison of categorical variables. p-value of <0.05 was considered using SPSS (Version 22). Results: 58 out of 300 women had Pelvic floor dysfunction. Majority of them 52 (17.33%) had Pelvic organ prolapse. Among them 43 (74.14%) women were >45 years old, 38 (65.52%) women had 2 or 3 children, and 12 (20.69%) women had ≥4 children. 47 (81.03%) had vaginal delivery. 37 (63.79%) subjects had no schooling and 13 (22.41%) were unskilled workers. 36 (62.07%) participants BMI ranged between 25 to 34.99. Age, education, occupation, number of children, mode of delivery, BMI were found to be associated with increased incidence of pelvic floor dysfunction. Conclusions: In conclusion the study assessed high prevalence of pelvic floor dysfunction associated with vaginal delivery, increased age, number of children and BMI.